Experimental orthotopic breast cancer as a model for investigation of mechanisms in malignancy and metastasis to the lymph nodes - Cesar Romero Soares Sousa; Ana Luisa Miranda-Vilela; Marcos Célio de Almeida; Juliana Menezes Soares Fernandes; Antonio Sebben; Sacha Braun Chaves; Kelly Grace Magalhães; Caroline Ribeiro da Silva; José Luiz Jivago de Paula Rôlo; Carolina Madeira Lucci; Zulmira Guerrero Marques Lacava (International Journal of Veterinary Science and Research - Peertechz Publications, 2019)
To understand the fundamental mechanisms behind malignancy of breast tumors and also contribute to the discovery of improved methods for prevention, diagnosis and treatment, animal cancer models remain essential. We aimed to establish an optimal orthotopic cancer model for breast cancer in the immunocompetent Swiss mouse, describing the detailed microanatomy of the mammary glands, the sentinel lymph node and lymphatic mapping, evaluating histopathological changes and characterizing the tumor by computed microtomography and interleukins expression. The inoculation of fresh Ehrlich tumor cells led to a detectable tumor as early as 24 hours later; after 7 days, mammary, muscular, dermal vascular and lymphatic invasion were observed and also micrometastases in mammary adipose tissue, sentinel lymph node and contralateral lymph node. From the inoculation site the tumor invaded the host mammary gland structures, the dermis and endomysium of skeletal muscle tissue. Type 1 T helper cytokine levels (IL-1β and IL-17) were significantly higher than anti-inflammatory Type 2 T helper (IL-4) after inoculation of fresh tumor cells. Differently, frozen tumor cells induced tumor development only 14 days after the inoculation while presenting expression of distinct interleukins. The set of findings indicates that orthotopic transplantation provides the microenvironment critical for cell interactions involved in the development of cancer and subsequent metastasis. In this regard, the anatomical and physiological knowledge of the mammary glands and ductal networks favor studies, diagnoses and therapies related to breast cancer and metastasis. Moreover, this study provides anatomical support for the understanding of the lymphatic spread process of cancer cells.